2014
DOI: 10.1155/2014/240581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regular Yogic Training on Growth Hormone and Dehydroepiandrosterone Sulfate as an Endocrine Marker of Aging

Abstract: Growth hormone (GH) and dehydroepiandrosterone sulfate (DHEAS) secretion decline with advancing age and are associated with the symptoms of aging. Yogic texts claimed that regular practice of yoga may restore and maintain general endocrinological properties in the human body. Objective of the Study. To observe the effect of yogic training for twelve weeks on basal level of GH and DHEAS in middle aged group. Method. Forty-five untrained volunteers were divided into two groups, that is, yoga practicing (experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…This integrated approach guarantees holistic benefits for the individual. Firstly, aerobic and anaerobic exercises improve the musculoskeletal structure, the insulin circuit, the hormone system, and the metabolism [39,40,41]. Furthermore, the benefits achieved from sports or gymnastic exercise are enhanced by the association with meditation activities and psychoanalytic techniques that help to induce relaxation and self-awareness; this technique helps to improve cognitive flexibility and increase attention, acceptance and control of emotional reactions [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…This integrated approach guarantees holistic benefits for the individual. Firstly, aerobic and anaerobic exercises improve the musculoskeletal structure, the insulin circuit, the hormone system, and the metabolism [39,40,41]. Furthermore, the benefits achieved from sports or gymnastic exercise are enhanced by the association with meditation activities and psychoanalytic techniques that help to induce relaxation and self-awareness; this technique helps to improve cognitive flexibility and increase attention, acceptance and control of emotional reactions [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…Yoga training was given by qualified yoga instructor for 60 min per day, 6 days per week for 12-week duration following a standard protocol. [ 16 ] The detail of yoga protocol is presented in Table 1 . Assessment of body composition and oxidant-antioxidant status was estimated among the groups.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to DHEA‐S levels, among the few existing studies researching other oriental psychosomatic methods, some of them coincide with results from our work (Carlson, Speca, Patel & Goodey, ; Vera et al ., ). Other studies, however, significant changes have reported (Chatterjee & Mondal, ; Glaser, Brind, Vogelman et al ., ; Walton, Pugh, Gelderloos & Macrae, ).…”
Section: Discussionmentioning
confidence: 87%